The Pastoral Epistles: Common Themes, Individual Compositions. Concluding Reflections - Porter, Stanley E. (Journal for the study of Paul and his letters, 2019)
This article responds to the five major presenters at the ETF Pastoral Epistles Symposium along several lines. I begin by introducing the importance of discussion of the Pastoral Epistles within the context of Continental European scholarship. The article is then divided into three substantive sections. The first identifies various common themes found within the five articles. These are related especially to matters of authorship as they pertain to accounting for variation among the letters. This variation is usually correlated with authorship, but more recent discussion regarding genre/register is also considered. A second section offers a brief summary and critique of each of the five articles, attempting to put each contribution within the context of the wider discussion. A third section offers summative observations.